Gamificación como estrategia para incluir la educación ambiental en el contexto universitario: caso REHI - Marlés Betancourt, Claritza; Peña Torres, Parcival; Pardo Rozo, Yelly Yamparli (Revista Científica, 2024)
This article describes an innovative classroom education experience through the design of a board game as a didactic alternative for introducing environmental education in university contexts. This experience considers the environmental realities of water resources and the impact of humans on them. An applied research work in the field of education is presented, which follows a mixed approach and implements the methodological phases of design-based research to address the collective construction of the game Reduce tu huella hídrica [Reduce your water footprint] with a research seed group via design thinking and gamification. In the different development stages, 106 students from Universidad de la Amazonía participated, who were selected by means of a non-probabilistic sampling. Among the results, the environmental awareness acquired by the participants stands out, with a positive assessment regarding the perceived appropriation of knowledge, the importance of the subject in the region, the game dynamics in terms of its ability to encourage attitude changes, and the methodological importance of gamification in the development of generic competencies such as teamwork, creativity, and communication. The board game designed represents a participative and flexible didactic alternative that contributes from academia to the construction of a water culture in the Amazon piedmont of Colombia.